Ecological Ethics and the Problem of Subject - Kalenda, Česlovas (Problemos, 2004)
The article analyses the theoretical experience of European philosophy about the interaction of man and nature. In the modern rationalistic philosophy the subject was reduced to human reason and opposed to the object, that is nature. Nature acquired, within the culture, the status of desubjectivized and de-ethicized reality. The objective German idealism of the 19th century overcame the categorical alienation of man from nature, while the philosophy of postmodernism disclosed it as a Western culture’s way of forcing human will upon nature, opening the perspective of subject’s decentration. The socio-ecological need to change man’s relation to nature prompts the following question: is it possible to understand a natural object as a subject? The article provides a version of a positive solution to this question.
Keywords: subject; object; importance of a thing; subjectification; respect for nature